Oversight on the Execution of Fixed-Term Employment Contracts at the Makassar City Labor Department - Amiruddin, Miftahul Chaer (Journal of Indonesian Scholars for Social Research, 2024)
This study delves into the procedures and regulatory frameworks governing PKWT, alongside scrutinizing the oversight mechanisms in place to ensure adherence to labor laws, safeguard worker rights, and maintain a balance between employer interests and employee protections. Through empirical legal research, involving interviews, document analysis, and a thorough review of legal statutes, the study unveils the intricacies of PKWT registration at the Makassar City Labor Office and assesses the effectiveness of labor oversight practices. Findings reveal that the registration process for PKWT, whether conducted online within three days or offline within seven days post-signing, necessitates the submission of specific documents to ensure legal and administrative compliance. This mechanism not only provides clarity and accountability but also serves as a foundational aspect of labor law enforcement. However, the research identifies a gap in the legal framework concerning sanctions for non-registration of PKWTs, underscoring a potential area for legislative enhancement to reinforce worker protections. The study further examines the role of labor oversight, conducted by the Makassar City Employment Office and other relevant bodies, in maintaining a fair, transparent, and regulated employment landscape. It categorizes oversight into preventive and repressive measures, each playing a critical role in promoting compliance with labor regulations and safeguarding worker rights. Despite the proactive efforts in education and socialization to foster compliance, limitations in authority at the city level underscore the necessity for coordinated efforts with provincial labor authorities to bolster oversight efficacy.